Mengkaji Dampak Dukungan Sosial, Optimisme, Religius, Dan Harga Diri Terhadap Kesejahteraan Subyektif Guru - Yuin, Komang; Agung, Anak Agung Gede; Dantes, Kadek Rihendra (Universitas Pendidikan Ganesha, 2024)
This study aims to assess the extent to which social support, optimism, religiosity, and self-esteem contribute to the subjective well-being of teachers in SMPNs across Mendoyo District. Additionally, it seeks to determine the combined impact of these factors on teachers' subjective well-being. This study is an